Exploring the potential of Fargesin from Chrysanthemum indicum for chronic migraine: in-silico and pharmacokinetic study - Rapuru Rushendran; Vellapandian Chitra (Future Science OA)
Introduction Chronic migraine is recognized by the WHO as one of the most debilitating chronic conditions. It is primarily caused by central sensitization of the trigeminal nucleus caudalis. Key biomarkers associated with migraine include NFkB, IL-1β, CGRP, and iNOS. While CGRP antagonists have proven effective in treating migraines, Chrysanthemum indicum L., a traditional herbal remedy, has not been established as a treatment.Methods To address this, we investigated whether Fargesin, a lignan found in CI, could potentially reduce migraines by targeting these biomarkers. We conducted pharmacokinetic, toxicological, and in-silico studies. Molecular docking studies revealed a strong interaction between Fargesin and CGRP/iNOS.Results The pharmacokinetic analysis indicated robust intestinal absorption and effective penetration of the blood-brain barrier. In-silico toxicity assessments showed favorable results. Promising interactions with drug targets were observed in bioactivity tests.Conclusion Fargesin from Chrysanthemum indicum may hold potential as a therapeutic agent for migraines.